2018
DOI: 10.1038/s41598-018-27958-1
|View full text |Cite
|
Sign up to set email alerts
|

Instability of personal human metabotype is linked to all-cause mortality

Abstract: Disruption of metabolic homeostasis is an important factor in many diseases. Various metabolites have been linked to higher risk of morbidity and all-cause mortality using metabolomics in large population-based cohorts. In these studies, baseline metabolite levels were compared across subjects to identify associations with health outcomes, implying the existence of ‘healthy’ concentration ranges that are equally applicable to all individuals. Here, we focused on intra-individual changes in metabolite levels ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 33 publications
2
16
0
Order By: Relevance
“…Hence, the majority of lipid species analyzed in our study showed evidence of stable individual differences for milk samples collected at different times of day (86.9% of lipid species, ICC > 0.4 and p < 0.05). Our findings are consistent with prior studies in which inter-individual variation was greater than intra-individual variation for lipids in milk [ 23 , 39 , 40 ] and blood plasma [ 41 ]. For example, one study of 52 women found that the variability of the lipid content in milk was four times higher between individuals than within individuals [ 39 ].…”
Section: Discussionsupporting
confidence: 93%
“…Hence, the majority of lipid species analyzed in our study showed evidence of stable individual differences for milk samples collected at different times of day (86.9% of lipid species, ICC > 0.4 and p < 0.05). Our findings are consistent with prior studies in which inter-individual variation was greater than intra-individual variation for lipids in milk [ 23 , 39 , 40 ] and blood plasma [ 41 ]. For example, one study of 52 women found that the variability of the lipid content in milk was four times higher between individuals than within individuals [ 39 ].…”
Section: Discussionsupporting
confidence: 93%
“…The lower levels observed in AD are in contrast to other complex phenotypes such as type 2 diabetes, insulin resistance, or obesity (66,73), where higher levels of BCAAs are found, and may indicate a switch to increased energy consumption via degradation of amino acids in AD. A recent study highlighted decreasing levels of valine as being significantly associated with all-cause mortality (74). Besides implications for energy metabolism, results from our study may thus characterize lower levels of valine also as a marker for increased female vulnerability to pathogenic processes in general and to βamyloidosis in AD in particular.…”
Section: Metabolic Effect Heterogeneity Suggests Sex-specific Differesupporting
confidence: 56%
“…The lower levels observed in AD are in contrast to other complex phenotypes such as type 2 diabetes, insulin resistance, or obesity 58,65 , in which higher levels of BCAAs are found, and may indicate a switch to increased energy consumption via degradation of amino acids in AD. A recent study reported decreasing levels of valine being significantly associated with all-cause mortality 66 . Besides implications for energy metabolism, results from our study may thus characterize lower levels of valine also as a marker for increased female vulnerability to pathogenic processes in general and to βamyloidosis in AD in particular.…”
Section: Discussionmentioning
confidence: 99%